2000
DOI: 10.1159/000052649
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic and Intelligibility Characteristics of Sentence Production in Neurogenic Speech Disorders

Abstract: The purpose of this study was to examine the relationship between scaled speech intelligibility and selected acoustic variables in persons with dysarthria. Control speakers and speakers with amyotrophic lateral sclerosis (ALS) and Parkinson’s disease (PD) produced sentences which were analyzed acoustically and perceptually. The acoustic variables included total utterance durations, segment durations, estimates of the acoustic vowel space, and slopes of formant transitions; the perceptual variables included sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
219
2
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(269 citation statements)
references
References 26 publications
(57 reference statements)
25
219
2
5
Order By: Relevance
“…For segmental measures, groups differed only in tense VSA and M1 differences for /t-k/. Similar to previous studies (Liu et al, 2005;Tjaden et al, 2013;Turner et al, 1995;Weismer et al, 2001), speakers with PD produced smaller articulatory working spaces, as indicated by smaller tense VSAs compared with the control group; however, no group differences were observed for lax VSA. Moreover, patterns of centralizing stop consonants, such as in Tjaden and Wilding (2004), were also observed for /t-k/ differences in speakers with PD from the current study.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…For segmental measures, groups differed only in tense VSA and M1 differences for /t-k/. Similar to previous studies (Liu et al, 2005;Tjaden et al, 2013;Turner et al, 1995;Weismer et al, 2001), speakers with PD produced smaller articulatory working spaces, as indicated by smaller tense VSAs compared with the control group; however, no group differences were observed for lax VSA. Moreover, patterns of centralizing stop consonants, such as in Tjaden and Wilding (2004), were also observed for /t-k/ differences in speakers with PD from the current study.…”
Section: Discussionsupporting
confidence: 84%
“…More recent acoustic studies have helped characterize the nature of the speech impairment in PD. For example, relative to healthy controls, speakers with PD produce more centralized vowel space areas (VSAs; Liu, Tsao, & Kuhl, 2005;Tjaden, Lam, & Wilding, 2013;Turner, Tjaden, & Weismer, 1995;Weismer, Jeng, Laures, Kent, & Kent, 2001), less spectrally distinct consonants (Tjaden & Wilding, 2004), weakened or less precise stop closures (Ackermann & Ziegler, 1991), and shallower second formant (F2) slopes, indicating slowed changes in vocal tract adjustments (Kent & Adams, 1989;Kim, Kent, & Weismer, 2011;Walsh & Smith, 2011). At the suprasegmental level, speakers with PD tend to pause more often (Torp & Hammen, 2000; but see Goberman & Elmer, 2005), utilize an increased fundamental frequency (F0; Canter, 1963;Goberman, Coelho, & Robb, 2002), and exhibit decreased variability in F0 (Canter, 1963(Canter, , 1965Flint, Black, Campbell-Taylor, Gailey, & Levinton, 1992;Skodda, Visser, & Schlegel, 2011a).…”
Section: Acoustic Characteristics Of Pdmentioning
confidence: 99%
“…In addition, there have been previous reports that speech in PD may be associated with a reduction in the size of the acoustic working space, which degrades perceptual impressions (Weismer, Jeng, Laures, Kent, & Kent, 2001;McRae & Tjaden, 2002). As a result, methods of rate reduction in PD have been a common treatment to improve speech intelligibility, as slowed speaking rates are associated with an expansion of acoustic working space (Weismer et al, 2001).…”
Section: Speech Rate Associated With Hypokinetic Dysarthriamentioning
confidence: 99%
“…These variables can be separated into those associated with the speaker, the listener, and contextual factors (Hustad & Weismer, 2007). Historically, research has focused on understanding how characteristics of the signal relate to intelligibility (see Kim et al, 2011;Turner, Tjaden, & Weismer, 1995;Weismer, Jeng, Laures, Kent, & Kent, 2001;Yunusova, Weismer, Kent, & Rusche, 2005). In recent years, efforts have focused on perceptual variables related to the listener in studies of intelligibility, including studies of perceptual learning in listeners when presented with dysarthric speech, as well as listening strategies and mechanisms Borrie, McAuliffe, Liss, O'Beirne, & Anderson, 2013;Choe, Liss, Azuma, & Mathy, 2012;Kim & Nanney, 2014).…”
mentioning
confidence: 99%